The prevalence of metabolic syndrome in children – a systematic review. (24th May 2012) - Friend, AJ; Craig, LCA; Turner, SW
Abstract : Introduction: Metabolic syndrome (MS) is a relatively recently coined term which refers to a combination of hypertension, abdominal obesity, impaired glucose tolerance and increased blood lipids. Although generally considered an adult disease, MS is now recognised in children, but how prevalent is MS among children? Estimating the true prevalence of this syndrome in children is difficult due to application of at least seven criteria. Our systematic review aimed to estimate the prevalence of metabolic syndrome in children by combining studies which used the same criteria and investigate the effects of diagnostic criteria, location and time. Methods: We carried out an OVID search using the terms metabolic syndrome X, obesity, hypertension, insulin resistance, child and adolescent and "prevalence". Results were limited to English language and humans. Studies were categorised as using world health organisation (WHO), international diabetes federation (IDF), adult treatment panel 3 (ATPIII) definitions. Results: A total of 450 abstracts were screened, and 109 papers reviewed of which 98 were included. For whole populations the prevalence of MS was 3-10% using ATP-based criteria and 1-7% for IDF. For populations of overweight/obese children the prevalence was 10-36% for ATP-based criteria, 16-44% for IDF criteria and 23-42% for WHO based criteria. Prevalence was never higher for girls than boys. When ATP-based studies of whole populations alone were considered (n=48), prevalence for surveys in the 1990s varied between 3-10% and 3-13% for surveys in 2000s. The MS prevalence was lowest for studies of European and Asian populations (3.3-4.2%) and highest for Middle Eastern and North American populations (4.2%-10%). The prevalence of MS in the UK general population is not known. The data found was collected between 1988 and 2010; however the earliest papers we found were published in 2004. Discussion: Different criteria for MS have been applied to paediatric populations and drawing conclusions is not without limitations; however the evidence is that MS is an increasingly prevalent chronic condition in children around the world. A lack of publications prior to 2004 may reflect an increased interest in the condition in recent years.